The Effects of Family Caps on the Subsequent Fertility Decisions of Never-Married Mothers - Wallace, Geoffrey L. (My University, 2007)
The author's estimates suggest that family caps designed to reduce fertility among welfare recipients by denying additional cash assistance to those who have children do not have an effect on subsequent child-bearing among never-married women.